Why do some African children develop severe malaria? - Greenwood, B; Marsh, K; Snow, R (1991)
Malaria is still a major cause of death and severe illness among children in many parts of tropical Africa, but only a small proportion of children, perhaps 1-2%, who become ill with malaria develop severe disease. Why only, some children experience a severe or fatal attack is not understood clearly. In this article, Brian Greenwood, Kevin Marsh and Robert Snow review some of those characteristics of the parasite and the host that may influence the outcome of a malaria infection. Identification of the relative importance of the many factors likely to be involved is needed in order to develop rational strategies for the prevention of deaths from malaria among children in malaria-endemic areas.